COMPARATIVE STUDY ON THE FINANCIAL PERFORMANCE OF INDONESIAN COMMERCIAL BANKS DUE TO THE CORONA VIRUS OUTBREAK - Natsir, Khairina; Arifin, Agus Zainul; Purwoto, Sutomo (International Journal of Application on Economics and Business, 2023)
This study intended to find out the differences in banking in Indonesia before and during the Covid-19 pandemic. The population is commercial bank companies listed on the Indonesia Stock Exchange, while the samples selected by purposive technique. The CAMELS method is used to assess banking performance. The data used in this study comes from the 2019-2020 quarterly financial statements. Statistical test using SPSS with Paired T-Test or Wilcoxon Signed-rank Test. In addition, the MANOVA test is used to determine whether there are significant differences in overall banking performance. The findings of this study are the Capital (CAR) has a significant difference in the first quarter of 2019 and 2020, Asset Quality (NPL) proxied by NPL-gross ratio has a significant difference in the second and third quarters, and NPL-net ratio has a significant difference in the fourth quarter, Management Quality (BOPO) have significant differences in the first, second, and third quarters, Earning (ROA) has a significant difference in the second and third quarters, Liquidity (LDR) ratio has a significant difference in the third and fourth quarters. Meanwhile, From the results of the MANOVA test on the performance of commercial banks, overall there is no significant difference due to the corona virus outbreak in Indonesia